2014
DOI: 10.1111/ijau.12033
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Characteristics and Audit Report Lag

Abstract: This study seeks to determine whether audit committee compositional features are associated with the timeliness of financial reporting by Australian firms. Timeliness of financial reporting by firms, of which the length of an audit is a fundamental component, adds information content and impacts firm value, making an examination of audit report lag determinants important. Results indicate that audit committee members with financial expertise, prior audit committee experience and those who are independent are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
225
6
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(301 citation statements)
references
References 82 publications
27
225
6
13
Order By: Relevance
“…They also found that this relation held for audit committee chairs. Sultana, Singh and Van der Zahn (2015) presented very similar findings for a sample of Australian companies. They suggested that regulatory requirements of audit committee independence and expertise could potentially improve financial reporting timeliness.…”
Section: Governancesupporting
confidence: 58%
“…They also found that this relation held for audit committee chairs. Sultana, Singh and Van der Zahn (2015) presented very similar findings for a sample of Australian companies. They suggested that regulatory requirements of audit committee independence and expertise could potentially improve financial reporting timeliness.…”
Section: Governancesupporting
confidence: 58%
“…Supporting this argument, Abernathy et al (2014) found that the presence and high proportion of accounting expertise on audit committees is associated with timelier audit reports for US companies. Baatwah et al (2015b) and Sultana et al (2015) also found that audit committees with financial expertise resulted in reduced audit report lag.…”
Section: Audit Committee Financial Expertisementioning
confidence: 94%
“…The motivation for this study stems from recent research that investigates the effect of corporate governance mechanisms on the timeliness of audit reports (e.g. Abdullah 2006;Afify 2009;Puasa, Salleh & Ahmad 2014;Abernathy, Beyer, Masli, & Stefaniak 2014;Baatwah, Salleh & Ahmad 2015b;Sultana, Singh & Van der Zahn 2015). In addition to investigating various corporate governance mechanisms, such as the board of directors and audit committee characteristics, previous research had also provided emphasis on the audit committee financial expertise since discharging audit committee responsibilities require directors with extensive financial knowledge and experience (Bédard, Chtourou & Courteau 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The framework of this research can be described in following Figure Meanwhile, Sultana et al (2015) try to exam whether audit committee compositional features are associated with the timeliness of financial reporting by Australian firms. They find that audit committee members with financial expertise, prior audit committee experience and those who are independent are associated with shorter audit report lag.…”
Section: Introductionmentioning
confidence: 99%